OP029 Characterisation of Paneth cell dysfunction in XIAP-deficient mice. (16th January 2018) - Yabal, M; Wahida, A; Popper, B; Steiger, K; Jost, P
Abstract: Background: A major cause of very-early onset inflammatory bowel disease (IBD) are primary immune-deficiencies (PID). One example is the X-linked lymphoproliferative syndrome type 2 (XLP-2) that is caused by deficiency in the X-linked inhibitor of apoptosis protein (XIAP). XLP-2 patients present with a plethora of symptoms that include hemophagocytic lymphohistiocytosis (HLH), recurrent splenomegaly and therapy refractory IBD which affects 20–26% of XLP-2 patients. Although many symptoms of XIAP-Deficiency have been associated with Epstein-Barr virus and other infections, the trigger behind the development of IBD remains elusive. Methods: This study is based on mouse models for XIAP-deficiencies, the Xiap–/– (complete loss of XIAP) and Xiap ΔD RING mice (a truncated form of XIAP). These mice mimic human patients who have no XIAP protein expression or express a truncated form of XIAP that lacks a functional ubiquitin-ligase domain, respectively. We have characterised the small and large intestine of these mice by immunohistochemistry, tandem electron microscopy, 16S sequencing of the microbiota and in vitro cultures of small intestinal organoids. We also examine the contribution of RIPK3 and TNF to the ileitis observed in XIAP-deficient mice. Results: Notably, both XIAP-deficient mouse lines develop spontaneous ileitis associated with microbial dysbiosis and a distinct metabolic signature. Preliminary data show that specifically Paneth and Lrg5+ stem cell compartments are perturbed due to loss of XIAP. The terminal ileitis is hallmarked by villous oedema and an increased influx of immune cells into the Lamina Propria of the small intestine. Our data suggest that the ileitis in Xiap–/– mice is triggered by microbiota and amplified by TNF-dependent signalling. We also examine the contribution of RIPK3 and cell death in deriving intestinal inflammation. Conclusions: Here we report the first comprehensive characterisation of intestinal inflammation in XIAP-deficient mice. We elucidate the signalling cascade that drives inflammation in the XIAP-deficient mice. Our work, therefore, constitutes a major advancement of our understanding of IBD in XLP-2 Syndrome.